PENGARUH KINERJA LINGKUNGAN DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN YANG DIMEDIASI OLEH REPUTASI PERUSAHAAN - Robert Jao; Kunradus Kampo; Anthony Holly; Raynold Kusnadi (Universitas Muhammadiyah Bengkulu, 2025)
This study aimed to partially examine the effect of environmental and financial performance on corporate reputation. Examine the effect of environmental performance and financial performance partially on firm value. It also tests the effect of environmental performance and financial performance partially on firm value through corporate reputation. The population used in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period, with a total sample size of 55 company data. This study's secondary data is the Annual and sustainability reports obtained from the Indonesia Stock Exchange (IDX) and the company's official website. The results of this study indicate that environmental performance has a positive and significant effect on corporate reputation. Financial performance has a positive and significant effect on corporate reputation. Corporate reputation has a positive and significant effect on firm value. Environmental performance has a positive but insignificant effect on firm value. Financial performance has a positive and significant effect on firm value. The results of this study also show that corporate reputation can mediate the relationship between environmental performance and firm value, and corporate reputation can also mediate the relationship between financial performance and firm value. Keywords: Environmental Performance, Financial Performance, Corporate Reputation, Firm Value